Comparison of Fatty Acid Profile and Proximate Composition of Three Native Trout Species: Health Benefits and Risk Assessments Associated with Their Consumption - Karsli, B; Çağlak, E; Kaya , C (Journal of the Hellenic Veterinary Medical Society, 2025)
Evaluating fish's nutrient content could provide essential guidance for fish consumption and the protection of human health. This study investigated the biochemical composition and fatty acid profiles (FA) of three native trout species: Salmo rizeensis, Salmo ardahanensis, and Salmo coruhensis. This is the first study to characterize FA content and lipid quality indices of S. rizeensis, Salmo ardahanensis, and S. coruhensis. The highest crude protein and crude fat were found in S. ardahanensis and S. rizeensis, respectively. Although there was no significant difference (p < 0.05) among trout species on crude protein, the crude fat content of S. rizeensis was significantly higher (p < 0.05) than the other species. The FA compositions of trout species ranged from 29.22% to 40.12% saturated FAs (SFA), 27.57% to 37.67% monounsaturated FAs (MUFA), and 26.54% to 28.41% polyunsaturated FAs (PUFA). The most dominant FAs were palmitic acid (C16:0) among SFAs, oleic acid (C18:1n9c) among MUFAs, and linoleic acid (C18:2n6c), eicosapentaenoic acid (EPA; C20:5n3) and docosahexaenoic acid (DHA; C22:6n3) among PUFAs. These species were found to be rich sources of EPA+DHA in the range of 10.49-15.58%. The highest fish lipid quality index (FLQ) and EPA+DHA content were found in S. ardahanensis, while the highest h/H value was in S. coruhensis. The atherogenic index, thrombogenic index, and ∑n-3/n-6 ratio of all species were within the limit range reported by international organizations. These results showed that all trout species used in this study could be considered as a beneficial and balanced food source for human consumption in terms of rich protein content, FA ratio, and lipid quality indices in future fish farming.